Development of business education in the Republic of Kazakhstan: challenges and solutions. (Journal of Economic Research & Business Administration, 2015)
The article deals with the business education development issues. The world trends in business education have been discussed; the situation in Kazakhstani business education and its providers have been analyzed.The author has revealed the factors that constrain the development of business education in Kazakhstan. It is emphasized that the main problem is a lack of a holistic concept as well as inadequate legislation in the fi eld of business education. Based on the results of research and literature analysis, practical recommendationson the improvement of business education system have been developed. It is supposed that implementation of these recommendations can radically improvethe training ofentrepreneurialand managerial skillsto the economy.The author concludes thatthe role of businessschools in theformation and development ofhuman resources is unprecedented. In conclusion it is emphasized thatfurther economic growthis impossible without welleducated and trainedmanagers. In many ways, the level of humancapital in the country, and the competitiveness of theeconomy will depend on the development ofbusiness education.
Keywords: business education; entrepreneurial and managerial staff; business school; MBA; DBA; human capital